FOXF1 ameliorates angiotensin II-induced cardiac fibrosis in cardiac fibroblasts through inhibiting the TGF-β1/Smad3 signaling pathway. (1st November 2020) - Jin, Daoxin; Han, Fangfang
Abstract: Cardiac fibrosis is a pathological feature common to a variety of heart diseases such as myocardial infarction, arrhythmias, cardiomyopathies and heart failure. The molecular mechanism underlying the cardiac fibrosis is still unclear. Forkhead box F1 (FOXF1), a member of the forkhead transcription factor superfamily, plays critical roles in the development of hepatic fibrosis. However, whether FOXF1 is involved in the pathogenesis of cardiac fibrosis remains to be elucidated. The present study aimed to investigate the role of FOXF1 and its mechanisms in regulating cardiac fibrosis. The results demonstrated that FOXF1 was downregulated in Ang II-induced CFs. Overexpression of FOXF1 inhibited angiotensin II (Ang II)-induced proliferation, migration and oxidative stress in cardiac fibroblasts (CFs). Overexpression of FOXF1 also reduced the expression of alpha-smooth muscle actin (a-SMA) in Ang II-induced CFs, suggesting that overexpression of FOXF1 prevented the differentiation of CFs to myofibroblasts. Furthermore, the production of extracellular matrix (ECM) components including type I collagen and fibronectin were reduced by overexpression of FOXF1 in Ang II-induced CFs. Furthermore, overexpression of FOXF1 prevented Ang II-induced activation of transforming growth factor beta 1 (TGF-β1)/Smad3 pathway in CFs. In conclusion, the results of the present study indicated that FOXF1 acted as a key regulator of pathological cardiac fibrosis, and overexpression of FOXF1 ameliorated cardiac fibrosis by inhabiting the TGF-β1/Smad3 signaling pathway. These results indicated that FOXF1 may be a novel target for attenuating cardiac fibrosis.